EXAMINING THE USE OF STYLE TO FOREGROUND THEMATIC CONCERNS IN RONALD ONTIRI ONCHURU’S POPULAR MUSIC - OSUBO, JOEL ATUTI (My University, 2023)
This study examined how Ronald Ontiri Onchuru, popularly known as Bikundo, deploys style to foreground particular thematic concerns in his popular music. Bikundo is one of the popular musicians among the Abagusii of western Kenya. The study was premised on the understanding that style is one of the tools available to creative artistes in articulating issues affecting their society. Consequently, it sought to analyse various features of style in Bikundo’s popular music and how they are used to bring out diverse thematic concerns in the music. The analysis was guided by the tenets of semiotics and sociological theories and was delimited to the analysis of Bikundo’s purposively sampled popular songs. Semiotics theory formed the bedrock of the study and helped in examining how aspects of style in Bikundo’s music articulate particular meanings in the songs. Sociological theory helped to show how Bikundo relied on context in foregrounding particular thematic concerns in his songs and how the songs applied to society. The study revealed that Bikundo uses various styles such as metaphor, symbolism, personification and idiomatic expressions to foreground themes such as HIV/AIDS, hardwork, poverty, and love. Through his popular music, Bikundo advocates for society which has a high regard for its morality, social cohesion and socio-economic empowerment.